DIRECT PLANTLET REGENERATION FROM SEGMENTS OF ROOT OF BALANITES AEGYPTIACA DEL. (L.)- A BIOFUEL ARID TREE - ANKITA VARSHNEY; MOHAMMAD ANIS (International Journal of Pharma and Bio Sciences, 2013)
Shoot organogenesis and plant establishment has been achieved for Balanites aegyptiaca (L.) Del. from excised root explants. Young root explants obtained from 4 weeks old aseptic seedlings were used for the induction of direct shoot regeneration by incorporating various cytokinins either singly or in combination with auxins in Murashige and Skoog (MS) basal medium. Root explants cultured on MS medium enriched with 5.0 µM Benzyladenine (BA) produced organogenic nodular meristemoids which developed into shoots at the cut ends as well as at the middle surface of the explant without formation of callus within 2 weeks of incubation. The highest frequency (68%) of shoot regeneration and maximum number (7.20 ± 0.15) of shoots per explant was obtained on MS medium containing a combination of 5 µM BA and 1.0 µM α- naphthalene acetic acid (NAA). The microshoots were rooted best on half strength MS medium supplemented with 1.0 µM indole-3-butyric acid (IBA). Plantlets derived via shoot organogenesis from root explants were successfully hardened and acclimatized under greenhouse and fared well with 75% survival rate in field conditions. The protocol could be harvested in obtaining biodiesel from the plants and genetic transformation for the benefit of mankind.